Influence of teacher's behavior and instructional management in students of intermediate english I level in the language department of the University of El Salvador in 2003 - Quijano Sandoval, Alba Claribel; Peña Díaz, Pedro Benigno; Salazar Murcia, Pedro Antonio (San Salvador : Universidad El Salvador, 2004)
The foreign language teaching profession today faces increasing enrollments and a shortage of qualified teachers. Curtain and Pesola (1994:24) say that “a foreign language teacher requires a combination of competences and background that may be unprecedent in the preparation of language teachers”. A second language teacher needs a higher standard of competencies like a high level of proficiency in the four skill (speaking, listening, reading and writing), the capacity to use the language in any social context, manage the content areas, knowledge of technologies, understanding of social, political, historical and economic reality of regions. A language teacher must have an extensive knowledge about different components of teaching in order to be prepared to make appropriate judgments and decisions about their teaching in the classroom. Professional growth (mentioned above) and aspects of their behavior such as: enthusiasm, attitude, personality and classroom management are involved on what is happening in their own classroom. Classroom management and teacher behavior are analyzed to find out their influence in students learning of English as a second language. Since teaching involves teacher’s behavior and actions, s/he needs to get acquainted of those that influence learning in a negative way as well as those influence positively the learning process.
Incluye anexos
Tesis (Licenciatura en Idioma Inglés opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2003
Bibliografía . h. 31
Keywords: Inglés -- Enseñanza; Profesores universitarios